Fear and its Movements: Comic Politics of Phóbos in Aristophanes’s Frogs - Buis, Emiliano Jerónimo (ΠΗΓΗ/FONS, 2020)
This paper aims to explore the comic allusions to fear as a passion that can shed light on the underlying dramatic coherence. In the first half of the comedy, Dionysus’s declared courage opposes his real fear, but the choral verses of the second part endorse a military harangue that intends to impose order and administer emotions to overcome fear. Against the private and apolitical fear which produces laughter at the beginning by immobilizing and depriving Dionysus of his citizenship, the play finally enshrines political phobos to mobilize and instruct the polis.